2016
DOI: 10.1155/2016/3495416
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Danger Signs of Obstetric Complications and Associated Factors among Postnatal Mothers of Mechekel District Health Centers, East Gojjam Zone, Northwest Ethiopia, 2014

Abstract: Background. Developing countries like Ethiopia contributed highest level of maternal mortality due to obstetric complications. Women awareness of obstetric danger sign to recognize complications to seek medical care early is the first intervention in an effort to decrease maternal death. Objective. To assess knowledge about danger signs of obstetric complications and associated factors among postnatal mothers at Mechekel district health centers, East Gojjam zone, Northwest Ethiopia, 2014. Methods. An instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
66
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(93 citation statements)
references
References 13 publications
20
66
2
2
Order By: Relevance
“…This is consistent with other studies done in low-income countries [11,12]. This is because educated women can easily understand health messages from different sources [11,12,28].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with other studies done in low-income countries [11,12]. This is because educated women can easily understand health messages from different sources [11,12,28].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, birth preparedness interventions help to address key bottlenecks to delays in deciding to seek care and reaching the place of care [6–9]. Comprehensive birth preparedness therefore enhances the ability of women, their partners, and families to engage in safe motherhood initiatives [10,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…Existing literature provides contrasting evidence regarding urban-rural disparity of knowledge. Results comparable to the present study were observed in some settings, 14 whereas in other settings a significantly higher knowledge of danger signs was observed among urban population. 8,9 This difference could be partially explained by the marked discrepancy of the accessibility of health care and availability of other facilities such as electronic media between different sectors in those countries.…”
Section: The Association Between the Level Of Awareness And Basic Chasupporting
confidence: 87%
“…Moreover, Public Health Midwives' services are freely available and accessible to all clients irrespective of income level, which may explain why income was not associated with level of awareness, though this finding is not in line with other research evidence. 7,14 Also, in consistence with previous studies conducted in Ethiopia, Malaysia and Nigeria, a good level of awareness on danger signs was significantly associated with higher educational levels of both pregnant mother and her husband and employment status of the pregnant mother. 7,9,11,13,14 As these variables are somewhat interconnected, the observed associations could be due to potential confounding effect mediated through high maternal health literacy.…”
Section: The Association Between the Level Of Awareness And Basic Chasupporting
confidence: 75%
See 1 more Smart Citation